(untitled) (Mediscope, 2025)
Background: Acute pancreatitis is a commonly encountered emergency in children but it has always been tough to predict accurately which subset of patients will become systemically unwell. Simple prognostic markers, such as red cell distribution width (RDW). This study was done to assess the usefulness of this marker. Methods: This observational study was conducted from July 2018 to June 2020 at the Department of Pediatric Gastroenterology and Nutrition, BSMMU, Dhaka. Thirty-one children with abdominal pain diagnosed with acute pancreatitis were included in the study. Results: The mean age of the pediatric patients was 11.19 (±3.45) years. The mean red cell distribution width was 14.99 (±2.96). RDW<14 was found in 15 cases (48.38%) and RDW ≥14 was found in 16 cases (51.62% Six patients (46.2%) with RDW<14 had complications while seven patients (53.8%) with RDW ≥14 had complications.). The mean Length of hospital stay (LOS) for RDW ≤14 group was 9.8 days while that of the RDW >14 group was 9.13 days. Conclusion: It was found that elevated RDW on admission had unfavorable clinical outcomes for pediatric patients with acute pancreatitis although statistical significance could not be established. Further multicenter studies with larger sample sizes are required to make some clinically applicable inferences. Mediscope 2025;12(1): 5-9